Pulp nerve fibers distribution of human carious teeth: An immunohistochemical study - Tetiana Haniastuti (Dental Journal (Majalah Kedokteran Gigi), 2010)
Background: Human dental pulp is richly innervated by trigeminal afferent axons that subserve nociceptive function. Accordingly, they respond to stimuli that induce injury to the pulp tissue. An injury to the nerve terminals and other tissue components in the pulp stimulate metabolic activation of the neurons in the trigeminal ganglion which result in morphological changes in the peripheral nerve terminals. Purpose: The aim of the study was to observe caries-related changes in the distribution of human pulpal nerve. Methods: Under informed consents, 15 third molars with caries at various stages of decay and 5 intact third molars were extracted because of orthodontic or therapeutic reasons. All samples were observed by micro-computed tomography to confirm the lesion condition 3-dimensionally, before decalcifying with 10% EDTA solution (pH 7.4). The specimens were then processed for immunohistochemistry using anti-protein gene products (PGP) 9.5, a specific marker for the nerve fiber. Results: In normal intact teeth, PGP 9.5 immunoreactive nerve fibers were seen concentrated beneath the odontoblast cell layer. Nerve fibers exhibited an increased density along the pulp-dentin border corresponding to the carious lesions. Conclusion: Neural density increases throughout the pulp chamber with the progression of caries. The activity and pathogenicity of the lesion as well as caries depth, might influence the degree of neural sprouting.Latar belakang: Pulpa gigi manusia diinervasi oleh serabut saraf trigeminal yang berespon terhadap stimuli penyebab perlukaan dengan menimbulkan rasa sakit. Perlukaan pada akhiran saraf dan komponen lain dari pulpa akan menstimulasi aktivasi metabolik dari neuron pada ganglion trigeminal sehingga mengakibatkan perubahan morfologi pada akhiran saraf perifer. Tujuan: Penelitian ini bertujuan untuk mengamati perubahan distribusi saraf pada pulpa gigi manusia yang disebabkan oleh proses karies. Metode: Penelitian ini menggunakan 15 buah gigi molar tiga yang mengalami karies dengan berbagai tingkat kedalaman karies dan 5 buah gigi molar tiga normal (tidak mengalami karies). Gigi-geligi tersebut dicabut untuk keperluan perawatan ortodontik atau alasan perawatan lainnya. Sebelum didekalsifikasi dengan menggunakan EDTA 10% (pH 7,4), seluruh sampel diamati dengan micro-computed tomography untuk mengetahui kondisi lesi secara tiga dimensi. Spesimen kemudian diproses secara immunohistokimia menggunakan anti-protein gene products (PGP) 9,5 yang merupakan penanda spesifik untuk serabut saraf. Hasil: Pada pulpa gigi normal, serabut saraf yang menunjukkan ekspresi PGP 9,5 positif tampak terkonsentrasi di bawah lapisan odontoblast. Distribusi serabut saraf tampak meningkat pada perbatasan dentin-pulpa di bawah lesi karies. Kesimpulan: Densitas serabut saraf pada kamar pulpa meningkat dengan bertambahnya kedalaman karies. Aktivitas dan patogenisitas dari lesi serta kedalaman karies dapat berpengaruh terhadap penyebaran serabut saraf.